Bogastvo in revščina v slovenski frazeologiji - Nikolovski, Gjoko (Slavia Centralis, 2023)
The purpose of the paper is to show the linguistic image of poverty and wealth through the prism of phraseological material from the Slovenian language The research material will be classified into two large groups, namely poverty and wealth, each of which is further divided into subgroups based on semantic analysis. The sociological view of both phenomena supports the initial hypothesis being that poverty is reflected in idioms associated with a lack of money, food, clothing, loss of home, debt and livelihood, while wealth is associated with birth rights, large amounts of money, well-being and a wasteful life-style.
Keywords: analize; analyses; bogastvo; frazemi; idioms; poverty; revščina; Slovene language; slovenščina; wealth